Computerized monitoring of patient-reported speech and swallowing problems in head and neck cancer patients in clinical practice - Cnossen, Ingrid C. (Springer-Verlag, 2012)
PURPOSE: The purpose of this study is to evaluate computerized monitoring of speech and swallowing outcomes and its impact on quality of life (QoL) and emotional well-being in head and neck cancer patients in an outpatient clinic. METHODS: Sixty-seven patients, treated by single or multimodality treatment, completed the EORTC QLQ-C30 and QLQ-H&N35 questionnaires and the Hospital Anxiety and Depression Scale in an outpatient clinic, using a touch screen computer system (OncoQuest), at baseline (at time of diagnosis) and first follow-up (1 month after end of treatment). RESULTS: Tumor sites included oral cavity (n = 12), oropharynx (n = 18), hypopharynx (n = 8), and larynx (n = 29). Tumor stage included carcinoma in situ (n = 3), stage I (n = 21), stage II (n = 7), stage III (n = 15), and IV (n = 21). No speech or swallowing problems at baseline or follow-up were noted in 23 % (speech) and 41 % (swallowing) of patients. Twenty-one percent (speech) and 19 % (swallowing) had problems at baseline and returned to normal scores at follow-up, while 16 % (speech) and 19 % (swallowing) had normal scores at baseline and developed problems at follow-up. Forty percent (speech) and 21 % (swallowing) had persistent problems from baseline to follow-up. At baseline, speech problems were significantly related to tumor site and emotional distress. At baseline and follow-up, swallowing problems were significantly related to QoL and emotional distress. At follow-up, speech problems were significantly related to QoL, emotional distress, and swallowing problems. CONCLUSIONS: Monitoring speech and swallowing problems through OncoQuest in an outpatient clinic is feasible. Many patients report speech and swallowing problems, negatively affecting their QoL and emotional well-being.